Intrinsic disorder in spondins and some of their interacting partners. Issue 1 (1st January 2016) - Alowolodu, Oluwole; Johnson, Gbemisola; Alashwal, Lamis; Addou, Iqbal; Zhdanova, Irina V.; Uversky, Vladimir N.
ABSTRACT: Spondins, which are proteins that inhibit and promote adherence of embryonic cells so as to aid axonal growth are part of the thrombospondin-1 family. Spondins function in several important biological processes, such as apoptosis, angiogenesis, etc. Spondins constitute a thrombospondin subfamily that includes F-spondin, a protein that interacts with Aβ precursor protein and inhibits its proteolytic processing; R-spondin, a 4-membered group of proteins that regulates Wnt pathway and have other functions, such as regulation of kidney proliferation, induction of epithelial proliferation, the tumor suppressant action; M-spondin that mediates mechanical linkage between the muscles and apodemes; and the SCO-spondin, a protein important for neuronal development. In this study, we investigated intrinsic disorder status of human spondins and their interacting partners, such as members of the LRP family, LGR family, Frizzled family, and several other binding partners in order to establish the existence and importance of disordered regions in spondins and their interacting partners by conducting a detailed analysis of their sequences, finding disordered regions, and establishing a correlation between their structure and biological functions.